2015
DOI: 10.1093/eurheartj/ehv115
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of atrial arrhythmia monitoring to guide anticoagulation in patients with implanted defibrillator and cardiac resynchronization devices

Abstract: IMPACT ClinicalTrials.gov identifier: NCT00559988 ( http://clinicaltrials.gov/ct2/show/NCT00559988?term=NCT00559988&rank=1 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
224
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 334 publications
(238 citation statements)
references
References 27 publications
2
224
1
11
Order By: Relevance
“…Much more frequently, the episodes occurred more than 30 days earlier, or occurred for the first time after a stroke [32]. Two further studies with similar methodologies also concluded that the majority of cardiac embolisms occur without immediately preceding episodes of atrial fibrillation [33,34]. Modern concepts are therefore based on the assumption that episodes of atrial fibrillation are only "the tip of the iceberg" and the epiphenomena of a complex disease of the atria, with risk of stroke persisting even after conversion to sinus rhythm [35,36].…”
Section: Embolies In Atrial Fibrillation: Complex Pathophysiologymentioning
confidence: 97%
See 1 more Smart Citation
“…Much more frequently, the episodes occurred more than 30 days earlier, or occurred for the first time after a stroke [32]. Two further studies with similar methodologies also concluded that the majority of cardiac embolisms occur without immediately preceding episodes of atrial fibrillation [33,34]. Modern concepts are therefore based on the assumption that episodes of atrial fibrillation are only "the tip of the iceberg" and the epiphenomena of a complex disease of the atria, with risk of stroke persisting even after conversion to sinus rhythm [35,36].…”
Section: Embolies In Atrial Fibrillation: Complex Pathophysiologymentioning
confidence: 97%
“…This approach appears to be intuitively correct but fails to convince as far an understanding of the large number of atrial fibrillation-associated stroke events is concerned. Most recently, newer data have raised serious questions about this approach [32][33][34]: In the AS-SERT study, involving 2 580 patients with implanted cardiac pacemaker or AICD aggregate groups, a total of 51 patients during follow-up of 2.5 years suffered an ischemic stroke or a systemic embolism. A reading of the pacemaker memory allowed to study the temporal relationship between atrial fibrillation episodes and the occurrence of stroke: In a period of 30 days before the occurrence of stroke, atrial fibrillation episodes > 6 min were detectable in only n 8 % of the cases.…”
Section: Embolies In Atrial Fibrillation: Complex Pathophysiologymentioning
confidence: 99%
“…48 In retrospect, this study likely failed due to low rates of AF (only 264 out of 2,718 patients had AF during the study); low rates of thromboembolism (only 69 patients experienced a thromboembolic event); and the fact that warfarin was the primary method of anticoagulation, with a suboptimal time in therapeutic range of approximately 59%. 49 More recent pilot studies using DOACs in lowto-intermediate risk patients with a low burden of AF, however, have shown more promising results. The Rhythm Evaluation for Anticoagulation with Continuous Monitoring (REACT.COM) pilot study was a multicenter single-arm study that enrolled 59 patients (mean age: 67 years ± eight years, 75% male, mean CHADS 2 score: 1.3 ± 0.5) with implanted Reveal XT™ (Medtronic, Minneapolis, MN, USA) ILRs; nonpermanent AF on a DOAC (apixaban, dabigatran, or rivaroxaban); and a CHADS 2 score of 1 to 2.…”
mentioning
confidence: 99%
“…7 Another puzzle is that asymptomatic episodes of SCAF detected by continuous monitoring in many, if not most, studies seem not to correlate closely with the timing of stroke. 4,[6][7][8]15 It may be that AF and thrombus formation might occur some days, weeks, or even months before the clot dislodges from the atrium and causes an embolic stroke, but it is difficult to incriminate AF as the stroke mechanism when the AF occurs only after the stroke. In addition, there are many causes of ischemic stroke other than AF, none of which is unlikely in patients with AF.…”
mentioning
confidence: 99%